2011
DOI: 10.1007/s00784-011-0560-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomised crossover trial to compare the potential of stannous fluoride and essential oil mouth rinses to induce tooth and tongue staining

Abstract: This study compared the staining potential of two experimental amine fluoride/stannous fluoride mouth rinses (A and B), a phenolic/essential oil rinse (C) and a negative control, water, rinse (D). The study was a single centre, randomized, single-blind, four treatment crossover study design among healthy participants. Prior to each study period, participants received a dental prophylaxis. On the Monday of each period, subjects suspended oral hygiene, and under supervision, rinsed with the allocated mouth rinse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
0
16
0
2
Order By: Relevance
“…Interestingly, in both, brushing and nonbrushing conditions, the antierosive effect of the F+LPP solution was similar to that of F+Sn. This is a promising result that warrants further investigation, as LPP does not have one important side effect associated with Sn-containing products, which is the potential for staining the tooth [West et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in both, brushing and nonbrushing conditions, the antierosive effect of the F+LPP solution was similar to that of F+Sn. This is a promising result that warrants further investigation, as LPP does not have one important side effect associated with Sn-containing products, which is the potential for staining the tooth [West et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…In a number of studies on AmF/SnF 2 mouth rinse, tooth discoloration was reported [8,24,25]. Recently, experimental AmF/SnF 2 rinses were tested but without any reduced staining effect [14]. New experimental formulations have been developed and tested in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…Sample size calculation, randomization and statistical analysis A detectable mean difference of 0.74 units in the primary parameter and a standard deviation representing the degree to which the outcome variable varies within subjects of 1.2 units were assumed based on the results of a former study that used the same design [14]. Sample size calculations were carried out by means of two tests at the global 5 % twosided alpha level for two Bonferroni adjusted contrasts with a power of 80 %.…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] SEM analyses were performed using 750-fold and 2000-fold magnifications as reported in other studies. [19][20][21][22] Nevertheless, the use of a 750-fold magnification can be considered more reliable for precise evaluation, as a relatively broad image is available for accurate quantification.…”
Section: Discussionmentioning
confidence: 99%